Comparison of HRM analysis and three REP-PCR genomic fingerprint methods for rapid typing of MRSA at a Brazilian hospital - Giovana Carolina Bodnar; Heloísa Moreira Martins; Caio Ferreira de Oliveira; Alexandre Tadachi Morey; Eliandro Reis Tavares; Juscélio Donizete Cardoso; Marcia Regina Eches Perugini; Lucy Megumi Yamauchi Lioni; Sueli Fumie Yamada-Ogatta; Renata Katsuko Takayama Kobayashi; Gerson Nakazato (Journal of Infection in Developing Countries)
Introduction: Infections caused by multidrug-resistant bacteria are increasingly common and represent a serious problem for public health. Staphylococcus aureus is one of the major agents of infections, and methicillin-resistant S. aureus (MRSA) has spread worldwide. The aim of this study was to phenotypically and genotypically characterize 55 MRSAs isolated in the University Hospital of Londrina, Paraná, Brazil, during 2010. Methodology: Bacterial isolates were characterized based on their antimicrobial susceptibility profile, biofilm production capacity, and staphylococcal chromosome cassette mec (SCCmec) type. Determination of clonal groups was performed by polymerase chain reaction using the RW3A, JB1, and BOX A1R primers and high-resolution melting (HRM) analysis. Results: The majority of isolates harbored SCCmec type II. SCCmec III, characteristic of the Brazilian endemic clone, was observed in four strains. Only two isolates harbored SCCmec type IV, which is common in community-acquired MRSA strains. Most isolates also showed resistance to more than four of the tested antimicrobials, and 30 isolates exhibited the ability to produce biofilm. DNA polymorphism analysis showed a higher discriminatory power for the JB1 primer, but RW3A revealed several clonal groups of MRSA with similar genotypic and phenotypic characteristics. HRM analysis showed eight different sequence types. Conclusions: These results are important for epidemiological studies involving MRSA infections.